Assessment of sociodemographic, health, and quality of life characteristics of elderly individual (Research, Society and Development, 2025)
Introduction: Interest in the study of aging and longevity has grown due to the specific health needs of the elderly population, especially concerning chronic diseases that affect quality of life and autonomy. Aging is a process of functional decline that compromises quality of life, and promoting healthy aging aims to optimize functionality by delaying pathological conditions. Objective: To assess the sociodemographic and health characteristics, as well as the quality of life, of elderly individuals. Methodology: This is a quantitative, descriptive, analytical, and cross-sectional study. A total of 301 elderly individuals, of both sexes, from a city in the interior of Minas Gerais, participated. A questionnaire on sociodemographic and health characteristics and the Elderly Quality of Life Scale were used. Results: 45.18% were between 70 and 79 years old, 54.15% were male, 54.15% lived with a partner, 60.13% followed the Catholic/Christian religion, 50.83% had more than five years of education, 64.11% had a monthly income between one and two minimum wages, 69.76% were diagnosed with Non-Communicable Chronic Diseases, 50.49% used polypharmacy, and 52.82% had comorbidities. Regarding the Elderly Quality of Life Scale, the classifications obtained were regular, good, and very good. Conclusion: The findings reinforce the need for strategies to promote healthy aging, aiming to minimize the physiological effects of senescence.